Djibouti : Requests for Disbursement Under the Rapid Credit Facility and Debt Relief Under the Catastrophe Containment and Relief Trust-Press Release; and Staff Report; and Statement by the Executive Director for Djibouti. (IMF Staff Country Reports; Country Report ;, 2020)
This paper highlights Djibouti's Requests for Disbursement Under the Rapid Credit Facility and Debt Relief Under the Catastrophe Containment and Relief Trust. The coronavirus disease 2019 pandemic is having a severe impact on Djibouti, creating urgent balance of payments and fiscal financing needs. The authorities acted swiftly to contain and mitigate the spread and impact of the virus. Their prevention and containment measures and decisions to scale-up health and other emergency spending to protect households and firms hit by the crisis will help limit economic and social consequences. IMF support is expected to provide additional resources for the essential health and other emergency spending, including social safety nets. It will also help catalyze additional donor support. Once the crisis abates, temporary measures should be unwound, with policies refocusing on promoting a strong and inclusive recovery and preserving medium-term debt sustainability. It will be critical to address and prevent the recurrence of external arrears, ramp up operations of key projects, and reduce public sector borrowing.